Change of viscosity of a suspension of cosmetic products during ultrafine grinding in bead mill - Hrininh-Hera, Kateryna; Omelianenko, Kostiantyn; Ponomarenko, Artem; Gubenia, Oleksii (My University, 2023)
Rheological characteristics effect on emulsification, transportation and also ensure proper consumer properties (spreadability, uniform distribution and fixation on the surface). The suspension was prepared according to the recipe: pigment iron oxide red 120 – 40% and castor oil – 60%. The duration of grinding is 45 minutes (2700 s). During grinding, the bead mill chamber was sampled every 5 minutes (300 s) to measure the shear stress at different values of the shear rate. The obtained results make it possible to monitor and adjust the necessary parameters of the ultrafine grinding process to achieve the required product quality.
Keywords: bead mill; бісерний млин; ultrafine grinding; кафедра мехатроніки та пакувальної техніки; подрібнення надтонке; ultrafine grinding